Using Two Predictor Scoring Systems Together to Increase the Chance of Identifying the Augmented Renal Clearance Phenomenon: A Cross-sectional Study (Iranian Journal of Kidney Diseases, 2022)
Introduction. Augmented Renal Clearance (ARC) reflects a measured creatinine clearance (CrCl) of more than 130 ml/min. Also, there are two scoring systems for the prediction of the ARC phenomenon i.e., the ARC score (ARCS) and the Augmented Renal Clearance in Trauma Intensive Care score (ARCTICs). The objectives of the current study were the evaluation the effect of using both scoring systems, on the chance of identifying this phenomenon and evaluating the accuracy of the three commonly used formulas for estimating glomerular filtration rate (eGFR) in ICU patients. Methods. In this prospective cross-sectional study, the CrCls of all patients admitted to the ICU were evaluated by using ARCS and ARCTICS, and for high-risk subjects based on scoring systems, a 12-hour urine sample was collected to measure CrCl. Besides, daily serum creatinine was recorded to estimate the daily eGFR. Results. During the study period, 810 subjects were evaluated and 145 were categorized as high-risk using scoring systems. The ARC phenomenon was confirmed in 79 patients on the recruitment day and 81.01 and 18.98% of them were recruited by ARCS and ARCTICS, respectively. The ROC curves showed AUCs > 0.5 for CockcroftGault (C-G) and CKD-EPI with the cut-off of 100.48 and 107.05 mL/min/ 1.73m2, respectively; to detect the ARC phenomenon. Conclusion. We recommend using ARCS and ARCTICS simultaneously to assess critically ill patients regarding the possibility of the ARC phenomenon which should be confirmed by using urinary CrCl, as none of the formulas could accurately detect the ARC phenomenon, neither the 12-hour CrCl.  DOI: 10.52547/ijkd.6695